A Stream Tapping Protocol Involving Clients in the Distribution of Videos on Demand. (29th April 2008) - Kulkarni, Santosh; Pâris, Jehan-François; Shah, Purvi
Abstract : We present a stream tapping protocol that involves clients in the video distribution process. As in conventional stream tapping, our protocol allows new clients to tap the most recent broadcast of the video they are watching. While conventional stream tapping required the server to send to these clients the part of the video they missed, our protocol delegates this task to the clients that are already watching the video, thus greatly reducing the workload of the server. Unlike previous solutions involving clients in the video distribution process, our protocol works with clients that can only upload video data at a fraction of the video consumption rate and includes a mechanism to control its network bandwidth consumption.